1990
DOI: 10.1346/ccmn.1990.0380508
|View full text |Cite
|
Sign up to set email alerts
|

Interstratification in Malawi Vermiculite: Effect of Bi-Ionic K-Mg Solutions

Abstract: Alrstract--The conversion of Malawi vermiculite into K-vermiculite by treatment with bi-ionic K-Mg solutions of 1 N total ion concentration (KC1 and MgCI2 mixed solutions of ionic strength equal to 0.5) was studied by following the 00l X-ray powder diffraction (XRD) reflections. Flakes of Mg-saturated samples were treated at 160~ during 24 hr with bi-ionic solutions, with the K concentration varying from zero to pure 1 N KC1 solution. The K-Mg interlayer exchange began at a critical value xK = .0196 (K/Mg = 1/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The divergent and receiving slits had respective openings of 1 ~ and 150 ~.m, and they allowed the sample to remain completely within the X-ray beam at all angles of 20. An angular geometric correction (Brindley and Guillery 1956) was used, along with corrections in intensity for Lorentz, polarization, geometric and absorption factors (Martin de Vidales et al 1990).…”
Section: Materials and Sample Preparationsmentioning
confidence: 99%
“…The divergent and receiving slits had respective openings of 1 ~ and 150 ~.m, and they allowed the sample to remain completely within the X-ray beam at all angles of 20. An angular geometric correction (Brindley and Guillery 1956) was used, along with corrections in intensity for Lorentz, polarization, geometric and absorption factors (Martin de Vidales et al 1990).…”
Section: Materials and Sample Preparationsmentioning
confidence: 99%
“…The theoretical profiles corresponding to different cases of 14/10 interstratification were calculated from the matrix expression developed by Plan~on (198 I), de la Calle andSuquet (1988), andPons et al (1990):…”
Section: Calculation Of the Theoretical X-ray Intensitymentioning
confidence: 99%
“…These diagrams permit rapid determination of the statistical parameters ofinterstratifications having d-spacings near 14.3 A and 10 J~ (notation: 14/10), and were derived from the theoretical X-ray diffraction intensity (de la Suquet 1988, Pons et al 1989). They are limited to interactions between nearest neighbors because interaction over a larger distance has not been found in interstratified Mg-vermiculite/K-vermiculite (Martin de Vidales et al 1990, 1991 or in chlorite interstratifications (Reynolds 1980(Reynolds , 1988.…”
Section: Introductionmentioning
confidence: 99%
“…Under these conditions, an angular geometric correction (Brindley and Gillery, 1956) was used. The experimental intensity was corrected for Lorentz, polarization, geometric and absorption factors (Martin de Vidales et al, 1990). Figure 2 shows the X-ray patterns corresponding to the Malawi vermiculite sample before and after treatment with the bi-ionic solution K/Mg = 1/5.…”
Section: Analysis Of the (0 O) Rodmentioning
confidence: 99%
“…By X-ray diffraction analysis along Z, Boettcher (1966), Rhoades and Coleman (1967), Sawhney and Reynolds (1985) and Martin de Vidales et aL (1990) showed that an intermediate interstratified slate is involved during the transformation from Mg vermiculite to K vermiculite.…”
Section: Introductionmentioning
confidence: 99%